2018
DOI: 10.22454/fammed.2018.794779
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in Residency: An Examination of Clinical Rotations and Competencies Where Family Medicine Residents Most Often Struggle

Abstract: The file review identified coronary care unit, internal medicine, obstetrics, and general surgery as those rotations (adjusted for length) where family medicine residents most often struggled. Furthermore, deficient clinical knowledge was not one of the main reasons that residents are flagged. These findings may inform programs about where to target resident supports and resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Professionalism is the most common reason for remediation, which is consistent with previous studies. 3,18 However, in contrast to these earlier studies, program directors reported that professionalism is not necessarily the hardest competency to successfully remediate. 19 A major challenge identified by 22% of respondents was a lack of documented evaluations to trigger or guide remediation (Table 4).…”
Section: Discussionmentioning
confidence: 85%
“…Professionalism is the most common reason for remediation, which is consistent with previous studies. 3,18 However, in contrast to these earlier studies, program directors reported that professionalism is not necessarily the hardest competency to successfully remediate. 19 A major challenge identified by 22% of respondents was a lack of documented evaluations to trigger or guide remediation (Table 4).…”
Section: Discussionmentioning
confidence: 85%
“…Residents lacking reliability from the perspective of the training staff were prevented to participate in shifts, emergency, or ICU wards through immediate dismissal for compelling reasons. As evidenced by the case law descriptions, the training staff appeared not to tolerate a combination of unreliability, untrainability, and incompetence in unpredictable environments with high demand for acute and critical emergency interventions [ 11 ]. Perceived future risks for patient safety were indeed accompanied reasons for dismissal in our case law, however, no incident was reported causing actual damage to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, assessing professional behaviour among GP residents remains a difficult task for staff delivering training [ 3 ], in part because of a lack of cultural consensus, and the resultant breadth of the definition of “high personal standards of behaviour” [ 4 ]. Despite this difficulty, assessing professionalism during residency is important because lapses in professional behaviour form a continuum from medical school to clinical practice [ 5 , 6 ], and are related to patient complaints [ 7 ] in both underperforming GPs and residents [ 8 , 9 ]. For patients, unprofessional behaviour of doctors (in training) might result in sub-optimal outcomes regarding patients’ health, safety, and care, undermining patients’ perceptions of the trustworthiness of the individual physician as well as the profession as a whole.…”
Section: Introductionmentioning
confidence: 99%